The contribution of order to the phase stability of β-Cu–Zn–Al - Lanzini, Fernando Gabriel (2011)
We report the lower stability temperatures, Tβ, of the bcc β phase for several alloys along the line of compositions Cu0.76-0.5x - Znx – Al0.24-0.5x, corresponding to a constant electron to atom ratio e/a = 1.48. The results have been obtained by means of differential scanning calorimetry (DSC) essays at various heating rates. The influence of atomic ordering on the stability of the bcc structure was evaluated using a mixed approach involving Monte Carlo simulations and the Cluster Variation Method. It was found that the chemical short and long range order contributes to the free energy of the alloy by an amount around 200 kB K.